(untitled) (Research, Society and Development, 2021)
With the objective of characterizing the inner traits of red-winged tinamou (Rhynchotus rufescens) eggs at reproductive phase and evaluate the effects of the storage on quality indicators, a total of 50 eggs were distributed in a completely randomized design and kept at room temperature for 28 experimental days. Average egg weight, Haugh unit, yolk index, width and height of yolk, albumen height, pH of internal components and yolk color were evaluated. Yolk color scores were determined by direct method of chromatic traits (parameters of lightness (L) and chromaticity (a *) (b *)). Assessments were made on days 0, 10, 15, 21 and 28 after laying. During the experimental period there was a reduction (p<0.05) of the Haugh unit and albumen height, albumen pH elevation (p<0.05), reduction (p<0.05) of redness (a*) and increased (p<0.05) yellowness (b*) in the yolk. Throughout the storage time, the average Haugh unit value declined from 84.74 to 41.59, albumen reduced average size into 4.37 mm and became more alkaline (final pH 9.58). The yolk presented itself yellowish, with an increase of 11.51 b* index and a reduction of -1.01 a* index. The other parameters of yolk quality were not affected (p>0.05) by the storage time. It is concluded, therefore, that red-winged tinamous eggs have internal characteristics with great potential for commercial exploitation. However, 28 days of storage at room temperature is enough to affect the albumen quality and yolk color.